Literasi Keuangan Gerakan Gemar Menabung Pada Anak Sekolah Dasar - Isnawati, Isnawati; Pancawai M., Rr. Sri; Lestari, Baiq Anggun Hilendri; Indriani, Eni (Dharma: Jurnal Pengabdian Masyarakat, 2025)
This activity aimed to cultivate a saving habit from an early age through direct financial literacy outreach in schools. The initiative was motivated by the relatively low saving culture among Indonesians compared to other Asian countries. Conducted on Tuesday, March 26, 2024, at SDN 01 Sugian, East Lombok, the outreach involved 63 students from grades 5 and 6. The program facilitated interactive communication between the presenter and the students, which enhanced the effectiveness of the material delivery. The activity successfully improved students’ understanding of the importance of saving and received positive responses from both teachers and parents. However, the increasing exposure of children to technology presents a challenge, as it raises concerns about their vulnerability to deceptive financial advertisements, including fraudulent investments. Therefore, continuous financial education is strongly encouraged by educators and parents to help students develop sound financial planning skills from an early age and to protect them from risks such as online gambling and unregulated online loans